Outbreak response management of a COVID-19 patient diagnosed on an open ward in Singapore - Pada, Surinder Kaur (International Journal of Infection Control, 2020)
We describe events leading to and actions taken to address a newly diagnosed COVID-19 case, admitted as dengue on the general ward. A risk Stratification strategy of patients into high, medium and low risk was considered for the isolation and COVID-19 swabbing strategies. Additional measures for cleaning and ward lockdown were also employed. There were a total of 191 exposures; 68 staff, 39 inpatients and the rest were community contacts. There was no transmission of COVID-19 in the 14 days following exposure, suggesting that a universal surgical mask and hand hygiene strategy in place at that time was sufficient in preventing transmission. The built environment of adequate bed-space and natural ventilation were other important considerations.